Korean species of the genus Neoperla Needham, 1905 (Plecoptera: Perlidae) - Murányi, Dávid; Li, Weihai; Jeon, Mi Jeong; Hwang, Jeong Mi; Seo, Hong Yul (Zootaxa, 2015)
Two new species of the perlid genus Neoperla, N. adamantea Murányi & Li, sp. n. and N. goguryeo Murányi & Li, sp. n. are described from both sexes, collected in the Kumgang and Myohyang Mountains of North Korea by personnel of the Hungarian Natural History Museum during the 1970’s. Two additional species, N. coreensis Ra, Kim, Kang & Ham, 1994 and N. ussurica Sivec & Zhiltzova, 1996 are redescribed from North Korean specimens. Neoperla quadrata Wu & Claassen, 1934 is redescribed on the basis of the holotype from Sichuan Province, China, and the Korean occurrence of this species requires confirmation. Korean and global distributions of the five Neoperla species reported from the peninsula are depicted on maps.